2017
DOI: 10.1021/acs.est.6b04998
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dual C–Cl Isotope Fractionation Patterns during Anaerobic Biodegradation of 1,2-Dichloroethane: Potential To Characterize Microbial Degradation in the Field

Abstract: This study investigates, for the first time, dual C-Cl isotope fractionation during anaerobic biodegradation of 1,2-dichloroethane (1,2-DCA) via dihaloelimination by Dehalococcoides and Dehalogenimonas-containing enrichment cultures. Isotopic fractionation of 1,2-DCA (ε and ε) for Dehalococcoides (-33.0 ± 0.4‰ and -5.1 ± 0.1‰) and Dehalogenimonas-containing microcosms (-23 ± 2‰ and -12.0 ± 0.8‰) resulted in distinctly different dual element C-Cl isotope correlations (Λ = ΔδC/ΔδCl ≈ ε/ε), 6.8 ± 0.2 and 1.89 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
50
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 49 publications
14
50
2
Order By: Relevance
“…(ε Cl bulk = -3.8 ± 0.2 ‰) (Palau et al, 2014). A recent study (Palau et al, 2017) with a Dehalococcoidescontaining enrichment culture showed a high similarity in chlorine isotope fractionation (ε Cl bulk = -5.1 ± 0.1 ‰) to the values observed in this study for pure cultures, but contrasted with anaerobic dihaloelimination by a Dehalogenimonas-containing enrichment culture,…”
Section: Chlorine Stable Isotope Analysissupporting
confidence: 66%
See 2 more Smart Citations
“…(ε Cl bulk = -3.8 ± 0.2 ‰) (Palau et al, 2014). A recent study (Palau et al, 2017) with a Dehalococcoidescontaining enrichment culture showed a high similarity in chlorine isotope fractionation (ε Cl bulk = -5.1 ± 0.1 ‰) to the values observed in this study for pure cultures, but contrasted with anaerobic dihaloelimination by a Dehalogenimonas-containing enrichment culture,…”
Section: Chlorine Stable Isotope Analysissupporting
confidence: 66%
“…Different studies have targeted aerobic degradation of 1,2-DCA using carbon and chlorine isotope fractionation to investigate the predominant reaction mechanism (Table 1) (Janssen, 1985, van den Wijngaard et al, 1992, Klečka et al, 1998, Hage & Hartmans, 1999, Hunkeler & Aravena, 2000, Hirschorn et al, 2004, Palau et al, 2014, Palau et al, 2017. While carbon isotope fractionation analysis is well established for decades, only recently developed methods enable chlorine and hydrogen analysis (Shouakar-Stash et al, 2005, Nijenhuis et al, 2016.…”
Section: Csia To Investigate 12-dca Dehalogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that contaminant concentration changes at the field are also related to processes other than its transformation (such as sorption and hydrodynamic dispersion), preventing accurate calculation of ε values. Thus, Λ values determined from laboratory studied reactions can be compared with those obtained from groundwater samples to investigate degradation processes at the field scale (Badin et al, 2014;Hermon et al, 2018;Hunkeler et al, 2009;Palau et al, 2017;Rodríguez-Fernández et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Hunkeler et al 9 and Breider et al 18 demonstrated the separation of natural from anthropogenic origins of chloroform using carbon (C)‐CSIA and chlorine (Cl)‐CSIA, respectively. Dual isotope data of C‐ and Cl‐CSIA reported by Palau et al 19 have shown a typical fractionation pattern for 1,2‐dichloroethane (1,2‐DCA) during reductive biodegradation in the field to distinguish aerobic from anaerobic conditions, and the same technique was used for pathway identification, 20 confirming CSIA as a powerful tool in environmental forensics.…”
Section: Introductionmentioning
confidence: 99%